Theory and calculation of heat transfer in furnaces - Zhang, Yanguo (Academic Press, an imprint of Elsevier, 2016)
Theory and Calculation of Heat Transfer in Furnaces covers the heat transfer process in furnaces, how it is related to energy exchange, the characteristics of efficiency, and the cleaning of combustion, providing readers with a comprehensive understanding of the simultaneous physical and chemical processes that occur in boiler combustion, flow, heat transfer, and mass transfer.
Keywords: Furnaces -- Combustion.; Boilers -- Combustion.; Heat -- Transmission.; elektronické knihy; electronic books